Pengembangan Aplikasi Pengelasan Berbasis Android sebagai Penunjang Belajar Siswa Kelas XI SMK Negeri Jawa Tengah - Rifqi, M. Irfan; Musyono, Ari Dwi Nur Indriawan; Rusiyanto, Rusiyanto; Kriswanto, Kriswanto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This research aims to develop an Android-based learning media in the form of a welding simulation application to support practical learning in Vocational High Schools (SMK). The background of this research is limited practical facilities, limited learning time, and low student engagement in direct welding practice. The method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate). The application was developed and validated by four experts, consisting of two material experts and two media experts. The validation results by the material experts showed a feasibility level of 87.25%, categorized as